2021
DOI: 10.3390/w13162159
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical Characterisation of High-Fluoride Groundwater and Development of a Conceptual Groundwater Flow Model Using a Combined Hydrogeological and Hydrochemical Approach on an Active Volcano: Mount Meru, Northern Tanzania

Abstract: This study characterises high-fluoride groundwater in the aquifer system on the flanks of Mount Meru, focusing on parts of the flanks that were only partially or not at all covered by previous research. Additionally, we analyse the impact of rainwater recharge on groundwater chemistry by monitoring spring discharges during water sampling. The results show that the main groundwater type in the study area is NaHCO3 alkaline groundwater (average pH = 7.8). High F− values were recorded: in 175 groundwater samples,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 31 publications
(73 reference statements)
0
42
0
Order By: Relevance
“…In the Arusha volcanic region in northern Tanzania, around Mount Meru, several studies with focus on F⁻ concentration in surface water (Kilham and Hecky, 1973;Nanyaro et al, 1984;Kitalika et al 2018) and groundwater (Ghiglieri et al, 2012;Chacha et al, 2018;Makoba and Muzuka, 2019;Bennett et al, 2021) have been conducted. The studies found that the general groundwater chemistry is F⁻-rich NaHCO3 alkaline water.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Arusha volcanic region in northern Tanzania, around Mount Meru, several studies with focus on F⁻ concentration in surface water (Kilham and Hecky, 1973;Nanyaro et al, 1984;Kitalika et al 2018) and groundwater (Ghiglieri et al, 2012;Chacha et al, 2018;Makoba and Muzuka, 2019;Bennett et al, 2021) have been conducted. The studies found that the general groundwater chemistry is F⁻-rich NaHCO3 alkaline water.…”
Section: Introductionmentioning
confidence: 99%
“…The studies found that the general groundwater chemistry is F⁻-rich NaHCO3 alkaline water. The main findings of these studies have been briefly summarised in the study of Bennett et al (2021), which described the hydrochemical characterisation of high-fluoride groundwater on the eastern, northern, western and south-western flanks of Mount Meru, the subject of a parallel to this paper. The studies that focused on the groundwater chemistry in the area found that rock mineral dissolution, water residence times (Ghiglieri et al, 2012;Chacha et al, 2018;Makoba and Muzuka, 2019;Ijumulana et al, 2020), exchange processes, calcite precipitation (Ghiglieri et al, 2012) and climatic conditions (temperature and rainfall), attributed to altitude and geographic positions (windward and leeward sides of Mount Meru) (Makoba and Muzuka, 2019) are controlling the groundwater chemistry in the area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potentiality of quality analysis to support groundwater management was highlighted by Benett et al [11]. They collect hydrochemical and hydrogeological data to study the high fluorite (F − ) groundwater concentration in an active volcano area of Tanzania.…”
Section: Vulnerability Assessment and Groundwater Qualitymentioning
confidence: 99%
“…The first theme concerns modelling efforts supporting the sustainable management of aquifer systems [8,9]. The second theme is focused on groundwater vulnerability assessments against external pollution, focusing on groundwater quality management [10][11][12][13]. The third theme explores the potentiality of geophysics tools supporting groundwater management in the case of coastal aquifers [14][15][16].…”
Section: Introductionmentioning
confidence: 99%